Effects of exogenous pyoverdines on Fe availability and their impacts on Mn(II) oxidation by Pseudomonas putida GB-1 - Lee, Sung-Woo; Parker, Dorothy L.; Geszvain, Kati; Tebo, Bradley M. (Frontiers in Microbiology, 2014)
Pseudomonas putida GB-1 is a Mn(II)-oxidizing bacterium that produces pyoverdine-type siderophores (PVDs), which facilitate the uptake of Fe(III) but also influence MnO2 formation. Recently, a non-ribosomal peptide synthetase mutant that does not synthesize PVD was described. Here we identified a gene encoding the PVDGB-1 (PVD produced by strain GB-1) uptake receptor (PputGB1_4082) of strain GB-1 and confirmed its function by in-frame mutagenesis. Growth and other physiological responses of these two mutants and of wild type were compared during cultivation in the presence of three chemically distinct sets of PVDs (siderotypes no1, no2 and no4) derived from various pseudomonads. Under iron-limiting conditions, Fe(III) complexes of various siderotype no1 PVDs (including PVDGB-1) allowed growth of wild type and the synthetase mutant, but not the receptor mutant, confirming that iron uptake with any tested siderotype no1 PVD depended on PputGB1_4082. Fe(III) complexes of a siderotype no2 PVD were not utilized by any strain and strongly induced PVD synthesis. In contrast, Fe(III) complexes of siderotype no4 PVDs promoted the growth of all three strains and did not induce PVD synthesis by the wild type, implying these complexes were utilized for iron uptake independent of PputGB1_4082. These differing properties of the three PVD types provided a way to differentiate between effects on MnO2 formation that resulted from iron limitation and others that required participation of the PVDGB-1 receptor. Specifically, MnO2 production was inhibited by siderotype no1 but not no4 PVDs indicating PVD synthesis or PputGB1_4082 involvement rather than iron-limitation caused the inhibition. In contrast, iron limitation was sufficient to explain the inhibition of Mn(II) oxidation by siderotype no2 PVDs. Collectively, our results provide insight into how competition for iron via siderophores influences growth, iron nutrition and MnO2 formation in more complex environmental systems.